Dampak Pandemi Covid-19 terhadap UMKM - Wiwin Wahyuni; Lilik Mardiana (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
This Covid-19 has had a bad impact on business and the economy, even business and economic uncertainty has become a very frightening specter for MSME actors. In order to maintain business continuity while at the same time saving the national economy, the government has implemented various socio-economic policy programs, including policy incentives and tax facilities that can be utilized by taxpayers. MSMEs are expected to boost economic growth and economic recovery. Through the empowerment of micro-enterprises, they can help people who have experienced layoffs and lost income because their businesses have been affected by the COVID-19 pandemic. The government can provide grants for start-up businesses. Among them are through people's business credit and providing loan repayment relief for MSMEs. The National Economic Recovery Policy (PEN) will encourage the re-growth of micro, small and medium enterprises. The government can provide grants for start-up businesses. Among them are through people's business credit and providing loan repayment relief for MSMEs. Nevertheless, he continued, it is necessary to increase cooperation between ministries, institutions, local governments, banking institutions, fintech, marketplaces, and all business actors so that they can compete in the market during this pandemic, support MSMEs to advance to class by helping implement digitalization of the environment. every step of daily business operations.